The use of inhaled nitric oxide in newborns with persistent pulmonary hypertension - Cynthia Reyes Flores (Medisur)
Persistent pulmonary hypertension in the newborn is a fatal condition in which the patient experiences severe respiratory distress and cyanosis, compromising his life. Within its therapy, the use of vasodilators such as nitric oxide plays an important role. The present bibliographic review aims to address the use of nitric oxide in newborns with persistent pulmonary hypertension. A search and documentary review was carried out in Spanish and English. Information from the last five years was collected using the Google Scholar search engine and in the SciELO, Lilacs and Pubmed databases. 21 documents that met the applied selection criteria were included in the analysis. It is a colorless and painless gas with an important, powerful and rapid vasodilatory function. The use of inhaled nitric oxide in neonates with persistent pulmonary hypertension has been investigated and questioned, however, it has been shown to be an effective treatment to improve oxygenation and reduce pulmonary arterial pressure in newborns with persistent pulmonary hypertension. Its vasodilatory effect helps to reduce pulmonary vascular resistance and improves respiratory function.